Ethical leadership and its role in enhancing organizational commitment: An analytical study of the opinions of a sample of workers in a number of private universities in the city of Sulaymaniyah / Kurdistan Region of Iraq - جاسم محمد وجدان (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The aim of this research to identify the role of ethical leadership in enhancing organizational commitment from workers view-point in a number of private universities operating in Sulaymaniyah governorate in Kurdistan region of Iraq, namely “Cihan, Qaiwan, and Komar universities”. Data was collected from (106) personal holding leadership positions; namely the university president and his deputies, deans and their assistants, head of academic and managerial departments, in addition to members of teaching staff. A simple random sampling method is used on data collected through questionnaires, and analyzed using the five-points Likert scale to understand the nature of the relationship between the ethical leadership variable which consists of “the availability of the ethical behavior, the practicality of ethical behavior and the promotion of ethical behavior”, and the dependent variable “organizational commitment”. The most important results that have been obtained were the presence of an average level of principle ethical leadership commitment at private universities (the research sample), as well as an average level of organizational commitment, as it was found, there is a direct correlation with a positive statistical significance of 0.571 between the level of ethical leadership and organizational commitment at the level of 0.01. As it was found that ethical leadership contributes to explaining 0.326 of the change in the organizational commitment variable, while the rest of the changes are due to other factors not included in the research model. The study recommends the necessity of conducting more studies and future research related to the factors affecting moral leadership and organizational commitment in order to identify the nature of this impact and work to find ways and methods through which to raise the level of these variables and achieve the best possible benefit from them and to spread the concept and culture of ethical leadership in all institutions. Working in Sulaymaniyah Governorate, providing programs and training courses for leaders and managers in various departments to work on raising their efficiency and increasing their ability to achieve the highest possible level of performance, working to implement the concept of organizational commitment in all institutions operating in Sulaymaniyah Governorate, and providing an appropriate work environment for employees.